DEVELOPMENT AND EVALUATION OF NANOPARTICLES BASED TRANSDERMAL PATCH OF AGOMELATINE FOR THE TREATMENT OF DEPRESSION - Shinde, Mahesh; Salve, Pramod; Rathod, Shahadev (Journal of Drug Delivery and Therapeutics, 2019)
Agomelatine (AGM) is an antidepressant drug. Its extensive hepatic first-pass metabolism coupled with low biological half-life shows 5% absolute bioavailability on oral administration. Polymeric nanoparticles (PNPs) have capability to efficiently penetrate the skin barrier and BBB so as to effectively reach the drug to site of action. Polymeric nanoparticles of drug (AGM-PNPs) with PLGA polymer were prepared by nanoprecipitation method followed by solvent evaporation. The particle size, polydispersity index, zeta potential and % entrapment efficiency of the optimized formulation were found to be compliant with the desired standards. DSC, FT-IR and XRD methods of instrumental analysis confirmed the formation of AGM-PNPs. Matrix–type transdermal patch containing AGM-PNPs (formulation TP 2) and AGM (formulation TP 1) were prepared by a solvent evaporation method using a film former machine. In-vitro drug release from patch formulations TP1 and TP2 were found to be 47.41 ± 1.78 and 70.16 ± 1.74. The drug release data of the in-vitro drug release study was analysed with kinetic models zero order, first order release kinetic model, Higuchi model, Korsmeyer-peppas model. In ex-vivo skin permeation studies, transdermal patch formulation containing AGMPNPs (TP 2) shown least lag time as compared to transdermal patch containing agomelatine (TP-1).